Down-Regulated Phosphoglycerate Kinase 1 Expression Is Associated With Poor Prognosis in Patients With Gallbladder Cancer. Issue 49 (December 2015) - Lu, Wei; Gao, Jian; Yang, Jingyun; Cao, Yang; Jiang, Lin; Li, Maolan; Zhang, Yijian; Zhou, Jian; Liu, Yingbin
Abstract : Abstract: To evaluate prognostic significance of phosphoglycerate kinase 1 (PGK1) protein expression in patients with gallbladder cancer (GBC). Ninety-five patients who underwent surgical resection for GBC between January 2004 and December 2010 were enrolled. Overall survival (OS) and disease-free survival (DFS) were evaluated over a 10-year follow-up. PGK1 expression was assessed by tissue microarray and immunohistochemistry. Prognostic significance was analyzed using multivariate Cox regression. PGK1 was highly expressed in all gallbladder mucosa. Decreased PGK1 expression was detected in 54.7% (52/95) of patients with GBC. It was significantly down-regulated in GBC samples compared with that in gallbladder mucosa ( P  < 0.0001), and was associated with multiple clinicopathological factors. Multivariate survival analysis showed that low PGK1 expression was associated with shorter OS (median 12.8 vs 45.4 months; hazard ratio [HR] = 3.077; 95% confidence interval [CI], 1.373–6.897; P  = 0.006) and DFS (median 8.3 vs 37.9 months; HR = 2.988; 95% CI, 1.315–6.790; P  = 0.009), indicating that PGK1 expression was an independent prognostic factor in patients with GBC. Low PGK1 expression was associated with progression in patients with GBC. PGK1 expression could be a useful prognostic biomarker for GBC. Abstract : Supplemental Digital Content is available in the text